The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.09.21.461198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dynamical Matryoshka model: 1. Incoherent neutron scattering functions for lipid dynamics in bilayers

Abstract: Fluid lipid bilayers are the building blocks of biological membranes. Although there is a large amount of experimental data using inconsistent quasi-elastic neutron scattering (QENS) techniques to study membranes, very little theoretical works have been developed to study the local dynamics of membranes. The main objective of this work is to build a theoretical framework to study and describe the local dynamics of lipids and derive analytical expressions of inconsistent diffusion functions (ISF) for QENS. As r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 23 publications
6
19
0
Order By: Relevance
“…This suggests that the local atomic motions of the tails are faster than those of the head groups. This is in good agreement with the Matryoshka model [21], where it was necessary to ascribe the contribution of the tail groups to the fast motions in order to fully account for the EISFs and QISFs of the current samples. Since the Matryoshka model was established independently of the width analysis of Lorentzian functions described in this paper, this agreement further enhances the validity of the Matryoshka model.…”
Section: Intermediate Motionssupporting
confidence: 82%
See 4 more Smart Citations
“…This suggests that the local atomic motions of the tails are faster than those of the head groups. This is in good agreement with the Matryoshka model [21], where it was necessary to ascribe the contribution of the tail groups to the fast motions in order to fully account for the EISFs and QISFs of the current samples. Since the Matryoshka model was established independently of the width analysis of Lorentzian functions described in this paper, this agreement further enhances the validity of the Matryoshka model.…”
Section: Intermediate Motionssupporting
confidence: 82%
“…In a previous QENS study on the bilayers of dipalmitoyl-phosphatidylcholine (DPPC) with and without deuteration of its tail group, the same tendency has been observed [29]. The EISF/QISF analysis by the Matryoshka model on the same samples has shown that the diffusion radius of the head group (d54DMPC MLB135) on the membrane plane is larger than that of the whole molecule [21,22]. Together with this finding, the present results imply that the head group of DMPC takes more time to explore the available space than the tail group.…”
Section: Slow Motionssupporting
confidence: 56%
See 3 more Smart Citations